(3GdETGQI Edi hajGJ GdCYjGf hGdefJbi ef JGQjN GdGSdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3YHO GdQMef Hf CMeO Hf eMeO GdfhjQi s)
(3ChdgG (B:s
(3CeG HYO aEf GdfHi Udi Gddg Ydjg hSde gGLQ Edi GdeOjfI s
(3BNQgG (B:s
(3GdfhjQi HdOG GdMfHdi ePgHG GdbGgQi ehdOkG YaG Gddg Yfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B82 - (3U(B182s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B18 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs